Patrimonialiser la culture : la mise en scène des rituels de possession en Uttarakhand - Serena Bindi (Anthropologie & Santé)
This article analyses the conflicting aspects of the process of patrimonialization of possession-based rituals in the North Indian State of Uttarakhand. The rituals are often altered in the heritage-making process. Rather than the important functions they hold within people’s ordinary experience or within the local therapeutic landscape, only some of the rituals’ esthetic aspects such as music, dancing, and singing are put forward. Although it is an integral component of the rituals when practiced within their original context, possession tends to be removed altogether when not reduced to being dramatized on stage. Despite such attempts to have it muted, local villagers practice possession during staged exhibitions of rituals which are often considered as being denatured. By defining possession as a cultural element worthy of representing them, these social actors thwart elitist efforts and demonstrate their aspiration to participate actively in heritage-defining discourses.